Phosphorus in the aerosols over oceans transported offshore from China to the Arctic Ocean: Speciation, spatial distribution, and potential sources - Chen, Sun; Zhouqing, Xie; Hui, Kang; Juan, Yu (Polar Research Institute of China - PRIC, 2015)
Atmospheric aerosol samples were collected from July to September 2008 onboard a round-trip cruise over the Eastern China Sea, Japan Sea, Western North Pacific Ocean, and the Arctic Ocean (31.1°N–85.18°N, 122.48°E–146.18°W). Total phosphorus (TP) and total inorganic phosphorus (TIP) were analyzed. The organic phosphorus (OP) was calculated by subtracting TIP from TP. Average concentrations of TP in the East Asia, Western North Pacific and Arctic Ocean were 7.90±6.45, 6.87±6.66 and 7.13±6.76 ng∙m-3, while TIP levels were 6.67±5.02, 6.07±6.58, and 6.23±5.96 along the three regions. TP and TIP levels varied considerably both spatially and temporally over the study extent. TIP was found to be the dominant species in most samples, accounting for 86.6% of TP on average. OP was also a significant fraction of TP due to the primary biogenic aerosol (PBA) contribution. The phosphorus in the atmospheric aerosol over the Arctic Ocean had a higher concentration than previous model simulations. Source apportionment analysis indicates that dust is an important phosphorus source which can be globally transported, and thus dust aerosol may be an important nutrient source in some remote regions.